PROCESSAMENTO E SINTERIZAÇÃO DA LIGA DE TUNGSTÊNIO USANDO COBRE INFILTRANTE, PARA BLINDAGEM DE RADIAÇÃO - FERREIRA SILVA, Victor Hugo; DE SOUZA, Armando Cirilo; MARTINEZ, Luis Gallego; QUEIROZ, Dalton Pedroso (ANAIS DO ENIC, 2017)
-